Dynamic fluctuations in brain iron content during migraine attacks: insights from relaxometry and diffusion tensor imaging - Birkl, Christoph; Filippi, Vera; Steiger, Ruth; Frank, Florian; Magnesius, Stephanie; Gizewski, Elke R.; Broessner, Gregor (Frontiers in Neurology, 2024)
BackgroundThere is evidence that iron metabolism may play a role in the underlying pathophysiological mechanism of migraine. Studies using R2∗ (=1/T2∗) relaxometry, a common MRI-based iron mapping technique, have reported increased R2∗ values in various brain structures of migraineurs, indicating iron accumulation compared to healthy controls.PurposeTo investigate whether there are short-term changes in R2∗ during a migraine attack.Population26-year-old male patient diagnosed with episodic migraine with aura according to ICHD-3 criteria.Sequence3 T, 64-channel head coil, for quantification of R2∗ relaxation a multi-echo gradient echo (GRE) sequence with TE = 4.92, 9.84, 14.7, 19.6, 24.6 and 29.51 ms, TR = 35 ms, flip angle = 15°, and 0.9 × 0.9 × 0.9 mm3 isotropic resolution was used.AssessmentQuantitative MRI, including R2∗ relaxometry and diffusion tensor imaging (DTI), was acquired from a migraine patient on 21 consecutive days, including migraine-free days and days with a migraine attack.Statistical testStatistical analysis was performed using R, the Shapiro–Wilk test, the t-test and Mann Whitney U test, analysis of variance (ANOVA) or Kruskal–Wallis test, depending on the distribution of the data. p-value <0.05 was considered significant.ResultsSignificant difference in R2∗ was found between the left and right hemispheres during a migraine attack. An increase in R2∗ was observed in the left hemisphere, whereas in the right hemisphere R2∗ was found to decrease. In the left cerebral white matter, R2∗ increased by 1.8% (p = 0.021), in the right cerebral white matter, R2∗ anisotropy decreased by 17% (p = 0.011) during a migraine attack.Data conclusionOur study showed a decrease and increase in iron content during the migraine cycle. Furthermore, during a migraine attack, white matter iron content increased, accompanied by a decrease in anisotropic tissue components, suggesting additional changes in vascular components.